The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/myc.13033
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based analysis of attributable hospitalisation costs of invasive fungal diseases in haematological malignancy patients using data linkage of state‐wide registry and costing databases: 2009‐2015

Abstract: Summary Background Invasive fungal diseases (IFD) are associated with significant treatment‐related costs in patients with haematological malignancies (HM). Objectives The objectives of this study were to characterise the gross and attributable hospitalisation costs of a variety of IFD in patients with HM by linking state‐wide hospital administrative and costing datasets. Patients/Methods We linked the Victorian Admitted Episodes Dataset, Victorian Cancer Registry and the Victorian Cost Data Collection from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…There are increasing numbers of immunosuppressed patients at risk of invasive fungal disease (IFD), 1,2 resulting in greater use of antifungal agents to prevent and treat IFD. 3 This, in turn, has led to increases in antifungal drug costs, 4,5 rates of adverse drug reactions 6 and drug-drug interactions. 7 These factors, in addition to the high mortality related to IFD [8][9][10][11] and the emergence of antifungal resistance, 12,13 necessitate the development of AFS programmes in hospitals to monitor and support optimal antifungal prescribing practices.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing numbers of immunosuppressed patients at risk of invasive fungal disease (IFD), 1,2 resulting in greater use of antifungal agents to prevent and treat IFD. 3 This, in turn, has led to increases in antifungal drug costs, 4,5 rates of adverse drug reactions 6 and drug-drug interactions. 7 These factors, in addition to the high mortality related to IFD [8][9][10][11] and the emergence of antifungal resistance, 12,13 necessitate the development of AFS programmes in hospitals to monitor and support optimal antifungal prescribing practices.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the incidence of proven or probable IFI was estimated at a rate of 2.1% per chemotherapy course, with a death rate of 11.7% according to data from the China Assessment of Antifungal Therapy in Hematological Diseases (CAESAR) study, which prospectively enrolled 4,192 patients undergoing chemotherapy for hematological malignancies at 35 Chinese hospitals ( 1 ). Patients with IFIs have been reported to have significantly increased hospitalization costs, which impose a heavy economic burden on the healthcare system worldwide ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly represented by a prolonged hospital length of stay (LOS) especially on the intensive care unit (ICU) and the need of expensive new class antifungal agents. Past studies reported additional direct treatment costs of patients with IFDs of up to €33,000 3–6 . Aspergillus and Candida species are the most common pathogens of IFD; however, the rising incidence of rare fungal infections, such as mucormycosis or fusariosis, represents an additional clinical and economical burden in the care for these patients 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Past studies reported additional direct treatment costs of patients with IFDs of up to €33,000. [3][4][5][6] Aspergillus and Candida species are the most common pathogens of IFD; however, the rising incidence of rare fungal infections, such as mucormycosis or fusariosis, represents an additional clinical and economical burden in the care for these patients. 7,8 Effective antifungal prophylaxis strategies after aSCT are needed to improve patient outcome and to prevent high additional treatment costs for healthcare systems.…”
Section: Introductionmentioning
confidence: 99%